Corrigendum to "Effects of particle composition on thorium scavenging in the North Atlantic" [Geochim. Cosmochim. Acta 233 (2018) 115–134]. (15th October 2018) - Lerner, Paul; Marchal, Olivier; Lam, Phoebe J.; Solow, Andrew
Abstract: The authors regret an error in Fig. 6 c, which incorrectly shows results from a regression performed using a nonlinear least squares procedure. Here we provide the corrected figure, which shows results from a regression performed using ordinary least squares.